Comparison of polyglycolic acid, polycaprolactone, and collagen as scaffolds for the production of tissue engineered intestine. Issue 3 (30th September 2018) - Liu, Yanchun; Nelson, Tyler; Chakroff, Jason; Cromeens, Barrett; Johnson, Jed; Lannutti, John; Besner, Gail E.
Abstract: Cell‐seeded scaffolds play critical roles in the production of tissue engineered intestine (TEI), a potential strategy for the treatment of short bowel syndrome. The current study compares polyglycolic acid (PGA), polycaprolactone (PCL), and collagen as scaffolds for TEI production. Tubular PGA scaffolds were prepared from nonwoven BIOFELT ® . Tubular PCL scaffolds were fabricated by electrospinning. Tubular collagen scaffolds were prepared using CollaTape, a wound dressing material. Both PGA and collagen were coated with poly‐l ‐lactic acid (PLLA) to improve scaffold mechanical properties. Pore size, porosity, microstructure, mechanical properties (suture retention strength and ultimate compressive force) were determined. The scaffolds were first seeded with crypt stem cells isolated from 1 to 3 day old rat pups and then implanted into the peritoneal cavity of nude rats. After 4 weeks of in vivo incubation, these cell‐seeded scaffolds were harvested for assessment of the TEI produced. Of the three materials compared, PLLA coated tubular PGA scaffolds had the appropriate pore size, mechanical properties and degradation rate leading to the production of TEI with an architecture similar to that of native rat intestine. © 2018 Wiley Periodicals, Inc. J. Biomed. Mater. Res. Part B, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 750–760, 2019.